Sedentary behaviours and cognitive function among community dwelling adults aged 50+ years: Results from the Irish longitudinal study of ageing. (October 2020) - Olanrewaju, O.; Koyanagi, A.; Tully, M.; Veronese, N.; Smith, L.
Abstract: Background: Sedentary behaviours (SB) are risk factors for poor cardiovascular health and all-cause mortality. However, their role in cognitive health in older adults is unclear. A few studies have examined associations between sedentary behaviours and cognition, but are limited by heterogeneity and insufficient longitudinal analyses. Therefore more robust studies, which would address identified limitations, are needed to accurately determine associations. Method: This study analysed data collected from participants aged 50+ years of The Irish Longitudinal Study of Ageing (TILDA). We conducted cross-sectional linear regression with multivariate imputation analyses of baseline data from wave 1 (N = 8163, weekday-sitting time), and wave 3 (N = 6400, weekday-television viewing); longitudinal analyses between waves 1–3 (sitting) and waves 3–4 (television). Sedentary behaviours were analysed as both categorical and continuous variables. Outcome of cross-sectional analyses was standardised regression co-efficient of associations between sedentary exposures and cognitive function in respective waves, while for longitudinal analyses was cognitive change (verbal memory, verbal fluency, and global cognition) between waves based on standardised residuals. Result: Study found significant but mild cross-sectional associations between 1-h increase in weekday-television viewing and poorer verbal memory (b = −0.02, CI: −0.04, −0.003, P < 0.05) and verbal fluency (b = −0.02, CI: −0.04, −0.002, P < 0.05). Baseline television viewing of 3.5+ h/day had mild but significant association with a decline in verbal fluency 2 years later in participants aged 65+ years, when compared with a reference category of <1.5 h of TV viewing (b = −0.12, CI: −0.23, −0.001, P < 0.05). Conclusion: Our study findings indicated some association between increased levels of weekday-television viewing time, independent of physical activity, and poor cognition cross-sectionally and longitudinally in middle-aged and older adults. Intervention studies are needed to confirm the effects of SB on cognition in older adults. Public health campaigns should be targeted at displacing high levels of television viewing, in excess of 3.5 h/day among older adults. Highlights: Effect of sedentary on cognition, independent of physical activity is unclear. 28% of community dwelling middle-aged and older adults reported 3.5+ h of television viewing per day during the weekday. Significant cross-sectional association between hourly increase of weekday-television viewing and poorer cognition in middle-aged and older adults. Significant longitudinal association between weekday-TV viewing in excess of 3.5+ h and decline in cognition in older adults aged 65+ years. Public health campaign should target reducing higher TV viewing (3.5+ h) in older adults.